Infrastruktura i material'naja baza fiziceskoj kul'turyj i sporta: perspektivy innovacionnogo vrazvitija - Polievskij, S. A.; Safranskaya, A. N. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The federal target program "Development of physical culture and sports in the Russian Federation in 2006-2015" is called upon to remove the number of the problems, negatively influencing the development of physical culture and sports and demanding the urgent solution. The authors analyze the prospects of this target program, and also advance arguments for its prompt introduction.